DINAMIKA PEMBAHASAN DAN PENGESAHAN PERATURAN DAERAH NOMOR 5 TAHUN 2016 TENTANG PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) KOTA PEKANBARU - Siti Maisarah; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In community empowerment to alleviate Pekanbaru City’s poverty issues. Pekanbaru City Government launched the Community Empowerment Program Based Rukun Warga or shortened by PMB-RW. However, in the discussion of local draft regulations on PMB-RW at the stage of meeting the formulation, they agreed to the establishment of PMB-RW is rejected, returned for revision and improvement by BAPPEDA, then there walked out number of Pekanbaru’s legislators include PDI-P, Nasdem and PPP in a plenary meeting. Based on the argument, the researcher wanted to know the dynamics that occur during the discussion and approval of the Provincial Regulation on PMB-RW Pekanbaru. The research is objective: First, to determine the stage of preparation of local draft regulations on PMB-RW. Second, to determine the stage of discussion. Third, to know the dynamics at the ratification local draft regulations on PMB-RW. This type of research is qualitative research methods. The location of this research is in BAPPEDA Office of Pekanbaru city and the Parliament Secretariat Office of Pekanbaru city. The data collected by completing the information through necessary interviews and requested documentation. While analysis of the data was performed using the method of qualitative analysis. Based on the result, the authors conclude that in the preparation of local draft regulations on PMB-RW is BAPPEDA had a problem at that time of collecting the data and information. After the exposition in this program turned out to be profitable and therefore the enactment of discretion. At the plenary meeting of the ratification local draft regulations on PMB-RW Pekanbaru number of legislators walked out because the legal framework is unclear and makes dual function of activities in Pekanbaru City Government.Keywords: PMB-RW, Dynamics, Counsil Of Pekanbaru City